17 PESAN DAKWAH RIKO THE SERIES - Afifi, Mohammad; As-Shobri, Ach. Faizal Umam (IDEALITA: Jurnal Pendidikan dan Sosial Keagamaan, 2023)
The cultivation of character values, especially those of a religious and social ethical nature, which are part of the preaching activities, should begin from an early age. The strategy of conveying and instilling these values can be done in various ways, one of which is by utilizing children's animated media that tends to be liked by children. In this research, the researcher explores the children's animated series "Riko The Series" in terms of the preaching messages conveyed. With the aim of exploring and interpreting the preaching messages present in "Riko The Series," the researcher conducted this study using a qualitative research approach through content analysis of the animation. The primary data source for this research is the video of "Riko The Series" episode 17, supplemented by information from the official website and other sources. This research focuses on the 17th episode of the animated series, which revolves around the main theme of "not getting angry." From this research, several preaching messages were obtained that emphasize important values in Islam and universal morals that can serve as lessons for child viewers. Some of these values include controlling negative emotions, starting with "Bismillah" (In the name of Allah), providing positive encouragement, asking questions and learning, offering advice and warnings, expressing gratitude and thankfulness, promoting justice and social ethics, awareness of mental health, respecting the will of Allah, and honesty.